Implementation of the golden age islamic boarding school program in improving the quality of life of elderly students at the Daarut Tauhiid Islamic Boarding School - Habibah, Nafahatul; Alawiyah, Mudrikah Romdona; Faujiah, Risnawati Sarifah; Muhyiddin, Afif Muhammad; Rosadi, Umar (ARKA INSTITUTE, 2024)
The Golden Age Program is a program that aims to foster Muslims and Muslim women at the golden age to have a straight creed, correct worship and noble character. In accordance with its title,